Place of Residence, Student Involvement, and First Year Marks - Grayson, J. Paul (Canadian Journal of Higher Education, 1997)
Research conducted in the United States has shown that students living in residence have greater gains in areas such as intellectual development, and are more likely to stay in university and complete their degrees, than students who live off-campus. The enhanced student involvement of those in residence is often cited in explanation for positive outcomes such as these. While there are some dissenting voices, research has also demonstrated that place of residence has little, if any, impact on marks. In a study of York University, a large commuter university, it is shown that place of residence does affect student involvement and first year marks; however, after controlling for OAC marks and faculty of enrollment, the first year marks of students who live at home with parents are higher than those of students in residence. Part of the explanation for this phenomenon can be found in the fact that despite their place of residence off-campus and low involvement in some activities, students living with their parents have higher rates of classroom involvement than students living in residence. In essence, living off-campus with parents does not represent a disadvantage in terms of first year marks.